Immunological Response of the Respiratory Tract in the SARS-CoV-2 Infection - Singh, Sanjiv; Aggarwal, Punita; Ravichandiran, Velayutham (Coronaviruses, 2021)
Severe acute respiratory syndromecoronavirus-2 (SARS-CoV-2) is a contagious pathogen responsible for the ongoing coronavirus disease 2019 (COVID-19) pandemic. The pathogenesis and immunological responses of SARS-CoV-2 infection are poorly understood until now. Once a person gets infected by SARS-COV-2, both innate and adaptive immunity gets compromised, which further plays an important role in making the disease more severe. The host's innate immune system forms the first layer of defense for protection from viral infections and initiates activation of the adaptive immune system in order to give maximum protection. The respiratory tract maintains the balance of T cell, B cell pro- and anti-inflammatory responses in order to protect the tissue from damage and diseases. In this review, the current updates related to the involvement of the immune system in the antiviral defense against SARS-CoV-2 have been discussed. These novel insights within the immunological response in the respiratory tract would support the future development of vaccines and immunoregulatory therapy for SARS-CoV-2 infection.
Keywords: T cell